The Application of Using Natural Reagent Extracted from Purple Sweet Potato for Naked-Eye Detection of Copper in Water Samples - Khaodee, Warangkhana; Wongkiti, Ratikon; Madang, Suphatta (Naresuan University Journal: Science and Technology (NUJST), 2018)
Reagent extracted from purple sweet potato was used to enable detection of Cu 2+ in water by the naked-eye. The optimum conditions for this were determined by adding 10 mL of reagent to a mixture of 500 mL of buffer pH 7 (0.01 M) and a 200 mL water sample. The lowest concentration of Cu 2+ able to be detected by the naked-eye was 3x10 -4 M without any interfering effects. This method was validated by comparing Cu 2+ concentration detected with the AAS technique. The results show that Cu 2 + concentrations obtained from both techniques were similar. Keywords: Purple sweet potato, Copper (II), Anthocyanin, Cyanidin, Naked-eye detection